2017
DOI: 10.1093/jisesa/iex003
|View full text |Cite|
|
Sign up to set email alerts
|

A General Approach to Test for Interaction Among Mixtures of Insecticidal Proteins Which Target Different Orders of Insect Pests

Abstract: A shift toward transgenic crops which produce combinations of insecticidal proteins has increased the interest (Syngenta Seeds, Inc., Minnetonka, MN) in studying the potential for interactions amongst those proteins. We present a general testing method which accommodates proteins with nonoverlapping spectrums of activity. Our sequential testing approach first investigates groups of the proteins with overlapping activity; e.g., proteins active against Lepidoptera or Coleoptera, respectively. The Colby method is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Similarly, a companion study with the same plant material did not report any effects when Bt maize pollen and T. urticae and R. padi reared on Bt maize were fed to the predators Chrysoperla carnea (Neuroptera: Chrysopidae), Phylloneta impressa (Aranea: Theridiidae), and Harmonia axyridis (Coleoptera: Coccinellidae) ( Svobodová et al, 2017 ). This supports the studies with sensitive herbivores that revealed no synergistic effects of different combinations of purified Cry proteins ( Raybould et al, 2012 ; Levine et al, 2016 ; Graser et al, 2017 ) or Cry proteins with dsRNA ( Levine et al, 2015 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, a companion study with the same plant material did not report any effects when Bt maize pollen and T. urticae and R. padi reared on Bt maize were fed to the predators Chrysoperla carnea (Neuroptera: Chrysopidae), Phylloneta impressa (Aranea: Theridiidae), and Harmonia axyridis (Coleoptera: Coccinellidae) ( Svobodová et al, 2017 ). This supports the studies with sensitive herbivores that revealed no synergistic effects of different combinations of purified Cry proteins ( Raybould et al, 2012 ; Levine et al, 2016 ; Graser et al, 2017 ) or Cry proteins with dsRNA ( Levine et al, 2015 ).…”
Section: Discussionsupporting
confidence: 86%
“…Potential interactions of different insecticidal proteins have been addressed in risk assessment studies using purified proteins and pest species that are sensitive to at least some of the used proteins. Graser et al (2017) for example demonstrated that three different lepidopteran-active Cry proteins (Cry1Ab, Cry1F, Vip3A) acted in an additive way in tests with lepidopteran larvae. However, two coleopteran-active proteins (eCry3.1Ab, mCry3A) showed possible slight antagonism in tests with a coleopteran species.…”
Section: Introductionmentioning
confidence: 99%
“…Different experimental approaches have been put forth to consider potential insecticidal protein interactions ( Tabashnik 1992 , Greenplate et al 2003 , Raybould et al 2012a , Tabashnik et al 2013 , Levine et al 2016 , Graser et al 2017 ), but they commonly rely on one of three models to interpret the additivity of tested components ( Table 1 ). Two of these somewhat related dose–response models, which have been utilized the most, have been termed ‘concentration addition’ (CA) or ‘response addition’ (RA), respectively.…”
mentioning
confidence: 99%
“…The Colorado potato beetle (CPB) insect diet (Frontier Scientific, Newark, DE, US) was freshly prepared for a diet incorporation bioassay as described in Graser et al (2017). The insecticidal activity of a mixture of eCry3.1Ab and mCry3A from (1) MZIR098 maize crude extract, (2) microbially produced eCry3.1Ab and mCry3A, and (3) nontransgenic maize crude extract fortified with a mixture of microbially produced eCry3.1Ab and mCry3A were determined in bioassays against first instar CPB larvae.…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…The bioassays were conducted in 24-well Costar culture plates (Corning, Inc., Kennebunk, ME, US) with each well containing one freshly hatched CPB insect larva as described in Graser et al (2017), except each well contained 200 ll of the respective diet mixture and plates were then stored at 22 ± 5°C, with a 14 h/10 h light/dark cycle. Plates were placed within the incubator in a non-systematic way, repositioning each successive day to minimize any potential systematic error associated with the environmental condition.…”
Section: Insecticidal Activitymentioning
confidence: 99%